2018
DOI: 10.1103/physrevb.97.201413
|View full text |Cite
|
Sign up to set email alerts
|

Persistent spin helix manipulation by optical doping of a CdTe quantum well

Abstract: Time-resolved Kerr-rotation microscopy explores the influence of optical doping on the persistent spin helix in a [001]-grown CdTe quantum well at cryogenic temperatures. Electron spin diffusion dynamics reveal a momentum-dependent effective magnetic field providing SU(2) spin-rotation symmetry, consistent with kinetic theory. The Dresselhaus and Rashba spin-orbit coupling parameters are extracted independently from rotating the spin helix with external magnetic fields applied parallel and perpendicular to the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 39 publications
1
7
0
1
Order By: Relevance
“…We emphasize that this peculiar spin wave mode emerges as an intrinsic property of the bulk phase, thus does not rely on fine tuning of Rashba and Dresselahus parameters which was a strong requirement to realize the PSH in semiconductor quantum wells explored in last years. [34][35][36][37][38][39] In particular, we have shown that the crystal symmetry (space group P 2 1 am) and the point group of the Γ point (C 2v ) around which the spin-splitting occurs, perfectly match the requirements for the PSH design, as it allows for coexisting Rashba and Dresselhaus couplings. Our DFT calculations reveal that these SOC parameters compensate well and the spin texture can be considered quasi-independent from the momentum.…”
Section: K • P Analysis Of Valence-band Spin Polarizationsmentioning
confidence: 71%
“…We emphasize that this peculiar spin wave mode emerges as an intrinsic property of the bulk phase, thus does not rely on fine tuning of Rashba and Dresselahus parameters which was a strong requirement to realize the PSH in semiconductor quantum wells explored in last years. [34][35][36][37][38][39] In particular, we have shown that the crystal symmetry (space group P 2 1 am) and the point group of the Γ point (C 2v ) around which the spin-splitting occurs, perfectly match the requirements for the PSH design, as it allows for coexisting Rashba and Dresselhaus couplings. Our DFT calculations reveal that these SOC parameters compensate well and the spin texture can be considered quasi-independent from the momentum.…”
Section: K • P Analysis Of Valence-band Spin Polarizationsmentioning
confidence: 71%
“…The dotted curve represents γ s calculated with the parameters of CdTe (E b = 10 meV, a B = 5.2 nm, δ e = 2π × 29 MHz) with n d = 10 14 cm −3 and γ D = 12µeV Å3 in the range of published values [35][36][37]. For this doping level one can distinguish the three different spin relaxation regimes.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…This twofold material choice is of great scientific interest as it allows for a comparison of the PSH characteristics in materials with different SO interaction strength. In addition, PSH physics in II-VI compounds has not been studied extensively [7,48].…”
Section: Sample Characteristics Of Cdte and Gaas Quantum Wellsmentioning
confidence: 99%
“…Thus, the value of l so,y observed at a specific delay time depends on the initial spot size w 0 and the diffusion coefficient D s [48]. 2together with other sample specific parameters.…”
mentioning
confidence: 99%